Results of Origami a Pleated Pentagon Dress Utilizing Shantung and Duchesse Fabrics - Aksari, Khairani; Nelmira, Weni (Gorga : Jurnal Seni Rupa, 2024)
Origami is a traditional Japanese paper craft technique that employs transformational reconstruction, a creative pattern-making method that creates a three-dimensional effect on fashion pieces. One notable design utilizing the origami technique is the origami a pleated pentagon dress. The construction of this dress is influenced by the type of material used. The primary objective of this research is to describe the outcomes of the origami a pleated pentagon dress using shantung and duchesse materials in terms of the stability of the origami shape, origami folds, and size accuracy. Additionally, it aims to identify the differences in the results obtained using these materials. This research falls under the category of applied research. The data collection method employed a questionnaire administered through a research instrument utilizing a Likert scale assessment conducted by 15 panelists. Data analysis techniques utilized quantitative descriptive and inferential analysis. The results obtained for the origami a pleated pentagon dress constructed using shantung material yielded an overall percentage value of 64.39%, categorized as quite suitable. Conversely, the results obtained for the origami a pleated pentagon dress constructed using duchesse material yielded an overall percentage value of 78.60%, categorized as suitable. Based on the independent sample t-test, the significance value obtained was 0.001< 0.05, indicating a difference in the results obtained using shantung and duchesse fabrics.